Återvinningsanläggningar för massor - En juridisk härva - Widström,Thelma (0349-4969, 2025)
The management of excavated materials is becoming more important as Sweden works towards climate neutrality. Improved coordination between construction projects and the use of local recycling facilities are seen as key to enabling circular mass management. However, the legislation governing the establishment and operation of mass recycling facilities is perceived as unclear, particularly regarding environmental permitting and the classification of excavated materials as waste or non-waste. This thesis focuses on facilities in Stockholm County where operations are subject to notification, C-activities, and do not need a full approval to operate their facility. The purpose of the thesis is to examine the requirements imposed on mass recycling facilities during environmental permitting, and how masses are managed at such facilities, as waste or non-waste. This is done to clarify the interpretation of applicable legislation. The study applies a combination of legal dogmatic method and EU legal method, complemented by a qualitative case study and semi- structured interviews with regulatory authorities, operators, and experts. The results show variation in legal interpretations across authorities. Existing case law and decisions on similar facilities often guide their assessments. Some specific precautionary measures frequently recur in decisions and can serve as general guidance, though a case-by-case evaluation remains necessary. Most operators avoid handling excavated materials as waste, and only a few undertake treatment to meet the criteria for waste cessation. The most challenging aspect of waste cessation is assessing whether use leads to general adverse effects on health or the environment. This assessment should be general yet is often applied in a site- specific manner. Early and well-supported evaluations are essential to enable more site-specific evaluations and hence enable more circular use of excavated materials.
Keywords: avfall; avfallsdefinitionen; biprodukt; end of waste; miljöprövning; återvinning; återvinningsanläggningar; återvinningsanläggningar för massor; massor; jordmassor; bergmassor; miljöfarlig verksamhet